Bioorthogonally surface‐edited extracellular vesicles based on metabolic glycoengineering for CD44‐mediated targeting of inflammatory diseases. Issue 5 (12th March 2021) - Lim, Gyeong Taek; You, Dong Gil; Han, Hwa Seung; Lee, Hansang; Shin, Sol; Oh, Byeong Hoon; Kumar, E. K. Pramod; Um, Wooram; Kim, Chan Ho; Han, Seungsu; Lee, Sangho; Lim, Seungho; et al.
Abstract: Extracellular vesicles (EVs) are essential mediators in intercellular communication that have emerged as natural therapeutic nanomedicines for the treatment of intractable diseases. Their therapeutic applications, however, have been limited by unpredictable in vivo biodistribution after systemic administration. To control the in vivo fate of EVs, their surfaces should be properly edited, depending on the target site of action. Herein, based on bioorthogonal copper‐free click chemistry (BCC), surface‐edited EVs were prepared by using metabolically glycoengineered cells. First, the exogenous azide group was generated on the cellular surface through metabolic glycoengineering (MGE) using the precursor. Next, PEGylated hyaluronic acid, capable of binding specifically to the CD44‐expressing cells, was labelled as the representative targeting moiety onto the cell surface by BCC. The surface‐edited EVs effectively accumulated into the target tissues of the animal models with rheumatoid arthritis and tumour, primarily owing to prolonged circulation in the bloodstream and the active targeting mechanism. Overall, these results suggest that BCC combined with MGE is highly useful as a simple and safe approach for the surface modification of EVs to modulate their in vivo fate.